Experiences and challenges of objective structured clinical examination (OSCE) as perceived by students and examiners in obstetrics and gynaecology: a phenomenological study - Orazulike, N (2024)
Introduction: The objective structured clinical examination (OSCE) is a global, high-stakes assessment introduced in Nigeria about three decades ago in a move which can be described as neo-colonial, transplanting systems practised in the developed countries without consideration of the African context. Documented advantages of the objective structured clinical examination such as its objectivity, increased student confidence, and a great platform for feedback abound in literature. However, it presents several challenges in implementation such as, a need for substantial human and material resources, the potential use of scenarios and subjects that might not mirror true life situations and its cost intensive nature especially in lower middle-income countries. Despite widespread adoption of this examination, its adoption in Nigerian medical schools and post graduate medical colleges have been relatively slow and unsatisfactory hence this study. Likewise, notwithstanding the strengths of the objective structured clinical examination, regular evaluations and feedback from relevant bodies which are crucial for refining its organisation, design and administration is lacking in Nigeria. This study assessed the experiences and challenges of the OSCE as perceived by students and examiners in obstetrics and gynaecology at the University of Port Harcourt, Nigeria and the Faculty of obstetrics and gynaecology, West African College of Surgeons.